A Short Review of Strategies for Augmenting Organism Recruitment on Coastal Defense Structures - Almog Ben-Natan; Nadav Shashar (Journal of Marine Science and Engineering)
The global demand for coastal urbanization is rising with the increasing population. Alas, living close to the ocean threatens human endeavors with high currents, waves, and increasing storm frequency. Accordingly, the need for more coastal defense structures (CDSs) rises. Structures built from complex units meant to prevent and/or mitigate coastal erosion and floods, additionally providing wave protection or wave attenuation, are constructed on and near natural habitats where they alter local ecosystems. Traditional CDSs mostly fail to harbor diverse and abundant communities. However, this can be changed by eco-friendly methodologies and designs that are being tested and implemented to improve CDSs’ ecological value. Some of these can be implemented during the construction period, while others can fit on existing structures, such as wave breakers and seawalls. Effective methods include augmenting surface rugosity through strategic perforations, integrating artificial panels for increased complexity, implementing soft (naturally based) engineering solutions such as geotextiles, replacing industrial concrete mixtures for CDS construction with “green concrete” and ecologically friendly mixtures, and using alternative, eco-friendly units in CDS erections. In this mini review, we suggest that by integrating sustainable practices into coastal development, we can significantly mitigate the ecological damage caused by traditional CDSs and promote more harmonious relationships between human construction and the marine environment. This shift towards environmentally conscious coastal defenses is essential and a responsibility for ensuring the long-term sustainability of our coastal communities and the health of our oceans. We present current methodologies used on breakwaters worldwide.